Pengaruh Kemudahan Transaksi dan Kepercayaan Pengguna terhadap Kepuasan Pengguna Fitur Shopee Paylater E-Commerce Shopee - Khasanah, Kholifatul; Aswad, Muhammad (Universitas Islam Nahdlatul Ulama Jepara, 2024)
The shift in people's attitude towards a completely digital system has prompted a rise in online shopping on different e-commerce platforms. Therefore, innovations have arisen from businesses in the electronic commerce industry, including the introduction of credit payment options. Shopee needs to create consumer satisfaction by implementing effective strategies, such as maximizing the use of their credit payment method called